Turbulent convection in round tube equipped with propeller type swirl generators - Eiamsa-ard, Smith; Rattanawong, Sarawut; Promvonge, Pongjet (My University, 2009)
This article is aimed at studying the heat transfer, friction loss and enhancement efficiency behaviors in a heat exchanger tube equipped with propeller type swirl generators at several pitch ratios (PR). The investigation is performed for the Reynolds number ranging from 4000 to 21,000 under a uniform heat flux condition. The experiments are also undertaken for several blade numbers of the propeller (N = 4, 6, and 8 blades) and for different blade angles (θ = 30°, 45°, and 60°). The influences of using the propeller rotating freely, on heat transfer enhancement, pressure loss, and enhancement efficiency, are reported. In the experiments, the swirl generator is used to create a decaying swirl in the tube flow. Average Nusselt numbers are determined and also compared with those obtained from other similar cases. The experimental results indicate that the tube with the propeller inserts provides considerable improvement of the heat transfer rate over the plain tube around 2.07 to 2.18 times for PR = 5, blade angles θ = 60° and N = 8. The use of the propeller leads to maximum enhancement efficiency up to 1.2. Thus, because of strong swirl or rotating flow, the propellers and their blade numbers become influential upon the heat transfer enhancement. The increase in friction factor from using the propeller is found to be 3-18 times over the plain tube. Correlations for Nusselt number (Nu) and friction factor (f) for the inserted tube are provided and the performance evaluation criterion to access the real benefits in using the swirl generators of the enhanced tube is also determined. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Decaying swirl flow; Enhancement efficiency; Heat transfer enhancement; Propeller; Swirl flow